Third Annual Report of Severn Wildfowl Trust: 1949-1950 - Anonymous, Anonymous (Wildfowl, 1950)
No abstract available. Contents include the following: WILD GEESE: Pink-footed Goose: Counts, Maximum Numbers since 1933, Total Numbers, Bean-Goose; White-fronted Goose: Counts, Proportion of Immature Birds, Family Size, Dominance Relationships, Marked and Distinguishable Geese, Rocket-nets, Migration Routes; Greenland White-fronted Goose, Lesser White-fronted Goose, Greylag Goose, Barnacle Goose, Canada Goose, Vegetation of the Dumbles, Proposed Bombing Range, Disturbance by Aircraft, Marking Operations away from the New Grounds. WILD DUCKS: The Decoy: The Lead, The Catch, Proposed New Decoy, Progress of Total Catch, Catch and Ringing, Methods of Capture; Status of Ducks: Shelduck, Pintail, Teal, Mallard, Gadwall, Wigeon, Garganey, Shoveler, Common Pochard, Tufted Duck; RINGING AND RECOVERIES (Anatidae): Birds Ringed, Recoveries, Proportion of Recoveries, Details of Recoveries, Map Showing Recoveries; BIRDS (Other than Anatidae) RECORDED AT THE NEW GROUNDS: Ringing of Birds other than Anatidae; OBSERVATION HUTS: Drawing of Observation Hut; WATERFOWL COLLECTION: New Species, Important Additions, List of Birds in the Collection, Hybrids, Obtaining New Birds; The Travelling Box, List of Species Required, Breeding Season, Hatching and Rearing, Eggs Left with Parents, Full-winged Birds, Wild Birds in the Pens, Pathology: Parasites, Diseases; Behaviour, Preening Studies, Research Facilities, THE NE-NE PROJECT; THE PERRY RIVER EXPEDITION, 1949: Preliminary Report, Capture of Live Geese for the Collection; GENERAL ACTIVITIES AND ADMINISTRATION: Visitors, Staff Arrangements, Membership, Finance, Lease and License, Bird Observatories Scheme, The Director’s Lectures, The Canal Lecture Tour, Market Harborough Festival, Arrangements for Visitors: Wild Geese, The Decoy, The Collection, Beatrice; Wants; THIRD ANNUAL GENERAL MEETING: Minutes, Income and Expenditure Account, Balance Sheet, Annual Dinner, Obituary; LIST OF MEMBERS; PHOTOGRAPHS; THE SWANS, GEESE AND DUCKS OF THE BRITISH ISLES: Swans, Black Geese, Grey Geese, Snow Geese.